The MEKANISASI BAGAN TANCAP MENGGUNAKAN ROLLER PENGANGKAT JARING DI PANGANDARAN, JAWA BARAT - Safingi Alamsah; Yaser Krisnafi; Arif Baswantara; Berbudi Wibowo; Regil Kentaurus Harryes (Bogor Agricultural University, 2021)
Pangandaran is located in the southern coast of the Java Island. Some of Pangandaran fishers operate lift net (bagan) to catch fish and shrimp. During hauling process, the net is lifted manually using a roller that potentially harm the fishers. The purpose of this study was to design a mechanical roller that applicable for lift net. The analysis of design requirement, such as calculation of torque, horse power, and reduction power with gear mechanism for operating the roller were applied in this research. The results showed that the net lifting operation required 4.8 HP or 3.6 KW of diesel engine to power a hydraulic pump. For the maximum load, when the net is fully loaded with fish, the operation required 67.91 HP or 50.64 KW. It means power from the diesel motor was not enough to support at maximum load. Therefore, a gear mechanism with a ratio of 1:14 was applied. However, this method reduces the angular speed of the gear which leads to reduction on net pulling speed. Keywords: Lift net, hydraulic, horse power, power, and lifnet roller